Criterion-related validity of self-screening using the KOJI AWARENESS™ test for range of motion and strength in healthy participants - Kenji Hirohata; Hidetaka Furuya; Sho Mitomo; Yuki Osaka; Koji Murofushi; Daisuke Yamaguchi; Kazuyoshi Yagishita (PLoS ONE, 2025)
Objective This study aimed to establish the validity of the KOJI AWARENESS™ sub-components by determining whether there is a connection between the sub-component scores and joint range of motion, muscle strength, and balance. Methods Fifty healthy adults (17 females and 33 males) participated in the study, completing the KOJI AWARENESS™ assessments and measurements of joint range of motion, muscle strength, and balance. The range of motion of the upper and lower extremities and trunk was measured using either a goniometer or an inclinometer. A handheld dynamometer was used to measure muscle strength. Balance ability was assessed using a modified balance error scoring system. Using the Mann–Whitney U test or the Jonckheere–Terpstra test, we compared KOJI AWARENESS™ scores with the corresponding body segments at a significance level of P ≤ 0.05. Results Our results indicated associations between external references and many items; however, no associations were found for flexion, extension, and rotation of neck mobility, extension and external rotation of hip mobility, and mid-section stability strength in KOJI AWARENESS™. Conclusion Overall, the KOJI AWARENESS™ sub-component scores demonstrated good validity, except for the items related to neck and hip flexibility and trunk muscle strength. Future analyses should include a wider range of age groups, such as middle-aged and older adults.